Analisis PAI Multidisipliner dalam Menjembatani Teologi dan Regulasi pada Kebijakan Lingkungan - Ali Samsi; Khodijatul Qodriyah; Veni Eka Yogawati; Dea Ayu Rozikin (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
This research aims to examine the role of multidisciplinary Islamic Religious Education as a bridge between theology and environmental regulation, as well as explore how the integration of faith values with environmental policies can shape the ecological awareness and social responsibility of students and educational institutions. A qualitative approach with a literature study design is used to search the literature, policy documents, and other relevant sources. Analysis techniques include data condensation, data reduction, data display, and data verification through content analysis to interpret the meaning of texts related to the relationship of theology, regulation, and practice of PAI. Multidisciplinary PAI is seen as a dialogue space that transforms Islamic teachings into a relevant ethical framework for ecological action and regulatory compliance. Integrasi teologi dan regulasi proven to increase the social legitimacy of environmental policies through the internalization of religious values in learning and practice in schools and communities. Environmentally integrated PAI learning practices show stronger opportunities for ecological behavior transformation than normative approaches alone. Conceptually, these results reinforce the idea that PAI is not just a subject but an ethical awareness-building mechanism that bridges faith, policy, and social action. Practically, curricula, teaching materials, and cross-disciplinary learning strategies that systematically link theology to environmental policy are needed to support equitable and sustainable policies.